Orthodontic treatment need in 14-16 year-old Tehran high school students - Safavi Seyed Mohammadreza; Sefidroodi Aliakbar; Nouri Mahtab; Eslamian Ladan; Kheirieh Sanam; Bagheban Alireza Akbarzadeh (Sciendo, 2023)
To assess orthodontic treatment need in a Tehran high school population.